Spiritual Leadership as a Catalyst for Fraud Prevention in Financial Services: Strengthening Economic Development Through Organizational Culture and Employee Motivation - Fahmy, Obaid Mujahid; Gunarsih, Tri; Wening, Nur (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to explore the impact of spiritual leadership on fraud prevention in financial service companies in Indonesia, focusing on the mediating role of organizational culture and the moderating effect of employee motivation. Employing a quantitative approach, the target population consists of all employees working in banking and non-banking financial service companies across several provinces in Indonesia. The 220 samples are selected through convenience sampling based on participants' availability and willingness. Data is obtained using a 5-point Likert scale questionnaire, and the analysis is conducted using descriptive statistics and Partial Least Squares (PLS) to test the hypotheses. The findings indicate that spiritual leadership significantly influences fraud prevention, both directly and through the organizational culture. Organizational culture effectively mediates the relationship between spiritual leadership and fraud prevention. However, employee motivation does not moderate this relationship. Interestingly, employee motivation does moderate the relationship between organizational culture and fraud prevention. These results imply that financial service companies should cultivate spiritual leadership and a solid organizational culture to enhance fraud prevention efforts while recognizing employee motivation's critical role in this context.